Measurement of the 92, 93, 94, 100Mo(γ, n) reactions by Coulomb Dissociation. Issue 1 (January 2016) - Göbel, K; Adrich, P; Altstadt, S; Alvarez-Pol, H; Aksouh, F; Aumann, T; Babilon, M; Behr, K-H; Benlliure, J; Berg, T; Böhmer, M; Boretzky, K; et al.
Abstract: The Coulomb Dissociation (CD) cross sections of the stable isotopes 92, 94, 100 Mo and of the unstable isotope 93 Mo were measured at the LAND/R 3 B setup at GSI Helmholtzzentrum für Schwerionenforschung in Darmstadt, Germany. Experimental data on these isotopes may help to explain the problem of the underproduction of 92, 94 Mo and 96, 98 Ru in the models of p-process nucleosynthesis. The CD cross sections obtained for the stable Mo isotopes are in good agreement with experiments performed with real photons, thus validating the method of Coulomb Dissociation. The result for the reaction 93 Mo(γ, n) is especially important since the corresponding cross section has not been measured before. A preliminary integral Coulomb Dissociation cross section of the 94 Mo(γ, n) reaction is presented. Further analysis will complete the experimental database for the (γ, n) production chain of the p-isotopes of molybdenum.